Copper-mediated reduction of azides under seemingly oxidising conditions: catalytic and computational studies. Issue 22 (16th October 2018) - Zelenay, Benjamin; Besora, Maria; Monasterio, Zaira; Ventura-Espinosa, David; White, Andrew J. P.; Maseras, Feliu; Díez-González, Silvia
Abstract : The reduction of aryl azides in the presence of water and air and without an obvious reducing agent is reported. Abstract : The reduction of aryl azides in the absence of an obvious reducing agent is reported. Careful catalyst design led to the production of anilines in the presence of water and air. The reaction medium (toluene/water) is crucial for the success of the reaction, as DFT calculations support the formation of benzyl alcohol as the oxidation product. A singular catalytic cycle is presented for this transformation based on four key steps: nitrene formation through nitrogen extrusion, formal oxidative addition of water, C(sp 3 )–H activation of toluene and reductive elimination.